Costa Rica y el Deporte (18731921) Un estudio acerca del origen del fútbol y la construcción de un deporte nacional - Urbina Gaitán, Chester (Editorial Universidad Nacional (EUNA), 2017)
This work is aimed at the national soccer (football) fan community. It is not limited only to stating names of sports events, players, associations and statistical data since, without wanting to dismiss the importance of the anecdotal element, it is even more edifying and beneficial to analyze the genesis of Costa Rican soccer (football) from a social perspective, based on its first reference in 1898, until 1921, the year in which it permanently and definitively acquired its federalization and the official status of national representation in the international arena.